A kind of microcrystalline glass and process

By optimizing the raw material composition and process flow of microcrystalline glass and adding specific intermediate oxides and network oxides, the problem of low strength of microcrystalline glass is solved, the effect of high strength and high hardness is achieved, and its application field is broadened.

CN118459099BActive Publication Date: 2025-02-25HENGSHUI JIXING ELECTRONIC MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410786766.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2025-02-25
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

The existing microcrystalline glass has low strength and is difficult to broaden its application areas.

Method used

By optimizing the composition of raw materials, zinc pyrostinate, zinc hypochlorite, phosphorus oxychloride and boron tribromide are added, and the glass liquid is formed and molded and Insulation is made to obtain high-strength microcrystalline glass.

Benefits of technology

It significantly improves the mechanical strength and hardness of microcrystalline glass, meeting a wider application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of microcrystalline glass, and proposes a microcrystalline glass and a process. The microcrystalline glass comprises the following components by mass: 50-60 parts of silicon dioxide, 15-25 parts of calcium oxide, 5-10 parts of magnesium oxide, 10-15 parts of aluminum oxide, 2-6 parts of zinc pyrostannate, 7-13 parts of zinc hypochlorite, 5-10 parts of ferric oxide, 1-3 parts of titanium dioxide, 1-4 parts of phosphorus oxychloride, and 4-9 parts of boron tribromide. The above technical solution solves the problem of low strength of microcrystalline glass in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microcrystalline glass, and in particular to a microcrystalline glass and a process. Background Art

[0002] Glass-ceramics are composite materials of evenly distributed microcrystals and glass phases, also known as glass ceramics or microcrystalline ceramics. They have high strength and good thermal and chemical stability and are widely used in defense, aerospace, electronics, chemical industry, biomedicine and other fields.

[0003] There are many types of glass-ceramics, which can be divided into high-strength glass-ceramics, corrosion-resistant glass-ceramics, low-expansion glass-ceramics, etc. according to their performance. The main production processes include melt-casting, sintering and sol-gel. The melt-casting method, also known as the overall crystallization method, is the currently commonly used glass-ceramics production process. The specific process is: after adding a certain amount of nucleating agent to the raw materials, melt them evenly to obtain glass liquid, anneal the glass liquid, nucleate, crystallize and re-anneal, and then obtain glass-ceramics.

[0004] The high strength of microcrystalline glass can greatly broaden the application field of microcrystalline glass. Therefore, how to provide a high-strength microcrystalline glass is a research hotspot in this field. Summary of the invention

[0005] The present invention provides a microcrystalline glass and a process, which solves the problem of low strength of the microcrystalline glass in the related art.

[0006] The technical solution of the present invention is as follows:

[0007] A microcrystalline glass, the raw materials of which include the following components in parts by mass: 50-60 parts of silicon dioxide, 15-25 parts of calcium oxide, 5-10 parts of magnesium oxide, 10-15 parts of aluminum oxide, 2-6 parts of zinc pyrostannate, 7-13 parts of zinc hypochlorite, 5-10 parts of iron oxide, 1-3 parts of titanium dioxide, 1-4 parts of phosphorus oxychloride, and 4-9 parts of boron tribromide.

[0008] As a further technical solution, the mass ratio of the phosphorus oxychloride and boron tribromide to zinc hypochlorite is 7-12:9.

[0009] The present invention limits the mass ratio of phosphorus oxychloride and boron tribromide to zinc hypochlorite to 7-12:9, thereby further improving the mechanical strength and hardness of the microcrystalline glass.

[0010] As a further technical solution, the mass ratio of the zinc pyrostannate to zinc hypochlorite is 4:9.

[0011] The present invention limits the mass ratio of zinc pyrostannate to zinc hypochlorite to 4:9, thereby further improving the mechanical strength of the microcrystalline glass.

[0012] As a further technical solution, the mass ratio of phosphorus oxychloride to boron tribromide is 1:3.

[0013] The present invention limits the mass ratio of phosphorus oxychloride to boron tribromide to 1:3, thereby further improving the mechanical strength and hardness of the microcrystalline glass.

[0014] The present invention also proposes a process for producing microcrystalline glass, comprising the following steps:

[0015] S1, mixing zinc hypochlorite, phosphorus oxychloride and boron tribromide, heating to 1400-1500°C and then heat preservation, adding the remaining raw materials, and introducing reducing gas for secondary heat preservation to obtain glass liquid;

[0016] S2, shaping the glass liquid, cooling it to room temperature, heating it to 600-800°C for three times of heat preservation, and cooling it to obtain microcrystalline glass.

[0017] As a further technical solution, the insulation time in S1 is 8 to 15 minutes.

[0018] As a further technical solution, the reducing gas in S1 includes one or both of hydrogen and carbon monoxide.

[0019] As a further technical solution, the secondary insulation time in S1 is 100-120 minutes.

[0020] As a further technical solution, the molding temperature in S2 is 500-550°C.

[0021] As a further technical solution, the three insulation times in S2 are 40 to 60 minutes.

[0022] The working principle and beneficial effects of the present invention are:

[0023] In the present invention, zinc pyrostannate and zinc hypochlorite are used to provide the intermediate oxide zinc oxide for the system, phosphorus oxychloride is used to provide the network oxide phosphorus pentoxide for the system, and boron tribromide is used to provide the network oxide boron trioxide for the system. By optimizing the introduction of raw materials and adding the intermediate oxide and the network oxide, the types of crystallization are increased, and the mechanical strength and hardness of the microcrystalline glass are improved. In addition, zinc pyrostannate can also provide tin dioxide as a clarifier for the microcrystalline glass, improve the defoaming ability of the microcrystalline glass, and achieve the effect of improving the mechanical strength and hardness of the microcrystalline glass. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] S1, 7 parts of zinc hypochlorite, 1 part of phosphorus oxychloride and 4 parts of boron tribromide were mixed, the temperature was raised to 1200°C at a heating rate of 20°C / min, and then the temperature was raised to 1400°C at a heating rate of 5°C / min, and the mixture was kept warm for 15 minutes, 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 6 parts of zinc pyrostannate, 5 parts of iron oxide and 1 part of titanium dioxide were added, hydrogen was introduced and kept warm for 120 minutes to obtain glass liquid;

[0027] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0028] Example 2

[0029] S1. Mix 13 parts of zinc hypochlorite, 4 parts of phosphorus oxychloride and 9 parts of boron tribromide, heat to 1200°C at a heating rate of 20°C / min, then heat to 1500°C at a heating rate of 5°C / min, keep warm for 8 minutes, add 60 parts of silicon dioxide, 25 parts of calcium oxide, 10 parts of magnesium oxide, 15 parts of aluminum oxide, 6 parts of zinc pyrostannate, 10 parts of iron oxide and 3 parts of titanium dioxide, and pass carbon monoxide for 100 minutes to obtain glass liquid;

[0030] S2. Transfer the glass liquid to a 550°C mold for molding. After cooling to room temperature, heat it to 800°C at a heating rate of 10°C / min, keep it warm for 40 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0031] Example 3

[0032] S1, 9 parts of zinc hypochlorite, 1 part of phosphorus oxychloride and 4 parts of boron tribromide were mixed, the temperature was raised to 1200°C at a heating rate of 20°C / min, and then the temperature was raised to 1400°C at a heating rate of 5°C / min, and the mixture was kept warm for 15 minutes, 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 4 parts of zinc pyrostannate, 5 parts of iron oxide and 1 part of titanium dioxide were added, hydrogen was introduced and kept warm for 120 minutes to obtain glass liquid;

[0033] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0034] Example 4

[0035] S1. Mix 11 parts of zinc hypochlorite, 1 part of phosphorus oxychloride and 4 parts of boron tribromide, heat to 1200°C at a heating rate of 20°C / min, then heat to 1400°C at a heating rate of 5°C / min, keep warm for 15 minutes, add 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 2 parts of zinc pyrostannate, 5 parts of iron oxide and 1 part of titanium dioxide, introduce hydrogen and keep warm for 120 minutes to obtain glass liquid;

[0036] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0037] Example 5

[0038] S1, 9 parts of zinc hypochlorite, 1.4 parts of phosphorus oxychloride and 5.6 parts of boron tribromide were mixed, the temperature was raised to 1200°C at a heating rate of 20°C / min, and then the temperature was raised to 1400°C at a heating rate of 5°C / min, and the mixture was kept warm for 15 minutes, 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 4 parts of zinc pyrostannate, 5 parts of iron oxide and 1 part of titanium dioxide were added, hydrogen was introduced and kept warm for 120 minutes to obtain glass liquid;

[0039] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0040] Example 6

[0041] S1, 9 parts of zinc hypochlorite, 2 parts of phosphorus oxychloride and 8 parts of boron tribromide were mixed, the temperature was raised to 1200°C at a heating rate of 20°C / min, and then the temperature was raised to 1400°C at a heating rate of 5°C / min, and the mixture was kept warm for 15 minutes, 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 4 parts of zinc pyrostannate, 5 parts of iron oxide and 1 part of titanium dioxide were added, hydrogen was introduced and kept warm for 120 minutes to obtain glass liquid;

[0042] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0043] Example 7

[0044] S1, 9 parts of zinc hypochlorite, 2.4 parts of phosphorus oxychloride and 9.6 parts of boron tribromide were mixed, the temperature was raised to 1200°C at a heating rate of 20°C / min, and then the temperature was raised to 1400°C at a heating rate of 5°C / min, and the mixture was kept warm for 15 minutes, 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 4 parts of zinc pyrostannate, 5 parts of iron oxide and 1 part of titanium dioxide were added, hydrogen was introduced and kept warm for 120 minutes to obtain glass liquid;

[0045] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0046] Example 8

[0047] S1, 9 parts of zinc hypochlorite, 2.6 parts of phosphorus oxychloride and 10.4 parts of boron tribromide were mixed, the temperature was raised to 1200°C at a heating rate of 20°C / min, and then the temperature was raised to 1400°C at a heating rate of 5°C / min, and the mixture was kept warm for 15 minutes, 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 4 parts of zinc pyrostannate, 5 parts of iron oxide and 1 part of titanium dioxide were added, hydrogen was introduced and kept warm for 120 minutes to obtain glass liquid;

[0048] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0049] Example 9

[0050] S1, 9 parts of zinc hypochlorite, 2.5 parts of phosphorus oxychloride and 7.5 parts of boron tribromide were mixed, the temperature was raised to 1200°C at a heating rate of 20°C / min, and then the temperature was raised to 1400°C at a heating rate of 5°C / min, and the mixture was kept warm for 15 minutes, 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 4 parts of zinc pyrostannate, 5 parts of iron oxide and 1 part of titanium dioxide were added, hydrogen was introduced and kept warm for 120 minutes to obtain glass liquid;

[0051] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0052] Example 10

[0053] S1, 9 parts of zinc hypochlorite, 4 parts of phosphorus oxychloride and 6 parts of boron tribromide were mixed, the temperature was raised to 1200°C at a heating rate of 20°C / min, and then the temperature was raised to 1400°C at a heating rate of 5°C / min, and the mixture was kept warm for 15 minutes, 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 4 parts of zinc pyrostannate, 5 parts of iron oxide and 1 part of titanium dioxide were added, hydrogen was introduced and kept warm for 120 minutes to obtain glass liquid;

[0054] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0055] Comparative Example 1

[0056] S1. Mix 13 parts of zinc hypochlorite, 1 part of phosphorus oxychloride and 4 parts of boron tribromide, heat to 1200°C at a heating rate of 20°C / min, then heat to 1400°C at a heating rate of 5°C / min, keep warm for 15 minutes, add 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 5 parts of iron oxide and 1 part of titanium dioxide, introduce hydrogen and keep warm for 120 minutes to obtain glass liquid;

[0057] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0058] Comparative Example 2

[0059] S1. Mix 1 part of phosphorus oxychloride and 4 parts of boron tribromide, heat to 1200°C at a heating rate of 20°C / min, then heat to 1400°C at a heating rate of 5°C / min, keep warm for 15 minutes, add 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 13 parts of zinc pyrostannate, 5 parts of iron oxide, and 1 part of titanium dioxide, and introduce hydrogen and keep warm for 120 minutes to obtain glass liquid;

[0060] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0061] Comparative Example 3

[0062] S1, 7 parts of zinc oxide, 1 part of phosphorus pentoxide and 4 parts of boron trioxide are mixed, the temperature is increased to 1200°C at a heating rate of 20°C / min, and then the temperature is increased to 1400°C at a heating rate of 5°C / min, and the temperature is kept for 15 minutes, 50 parts of silicon dioxide, 15 parts of calcium oxide, 5 parts of magnesium oxide, 10 parts of aluminum oxide, 6 parts of zinc oxide, 5 parts of iron oxide and 1 part of titanium dioxide are added, hydrogen is introduced and kept warm for 120 minutes to obtain glass liquid;

[0063] S2. Transfer the glass liquid to a 500°C mold for molding. After cooling to room temperature, heat it to 600°C at a heating rate of 10°C / min, keep it warm for 60 minutes, and cool it to room temperature to obtain microcrystalline glass.

[0064] The microcrystalline glasses obtained in Examples 1 to 10 and Comparative Examples 1 to 3 were tested for bending strength and Mohs hardness according to the method in JC / T 872-2019 “Microcrystalline Glass for Architectural Decoration”, and the test results are recorded in Table 1.

[0065] Table 1 Bending strength and Mohs hardness of glass-ceramics

[0066]

[0067] It can be seen from Table 1 that the bending strength of the microcrystalline glass obtained in Examples 1 to 10 of the present invention is above 40.99 MPa and the Mohs hardness is above level 6. The remaining properties are also in line with the performance requirements of JC / T 872-2019 "Microcrystalline Glass for Architectural Decoration" through testing.

[0068] Compared with Comparative Examples 1 to 3, in Example 1, zinc pyrosteinate, zinc hypochlorite, phosphorus oxychloride and boron tribromide are added as raw materials for microcrystalline glass, and the bending strength and Mohs hardness of the obtained microcrystalline glass are higher than those of Comparative Examples 1 to 3, indicating that the mechanical strength and hardness of the microcrystalline glass can be improved by synergistically providing the intermediate oxide zinc oxide to the system, phosphorus oxychloride to the system to provide the network oxide phosphorus pentoxide, and boron tribromide to provide the system to provide the network oxide boron trioxide.

[0069] The bending strength of the glass-ceramics obtained in Example 3 is higher than that in Example 1 and Example 4, indicating that the mass ratio of zinc pyrostannate to zinc hypochlorite is 4:9, which can improve the mechanical strength of the glass-ceramics; the bending strength and Mohs hardness of the glass-ceramics obtained in Examples 5 to 7 are higher than those in Example 3 and Example 8, indicating that the mass ratio of phosphorus oxychloride and boron tribromide to zinc hypochlorite is 7 to 12:9, which can further improve the mechanical strength and hardness of the glass-ceramics. The bending strength and Mohs hardness of the glass-ceramics obtained in Example 9 are higher than those in the other examples, indicating that the mass ratio of phosphorus oxychloride to boron tribromide is 1:3, which can further improve the mechanical strength and hardness of the glass-ceramics.

[0070] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A glass-ceramic, characterized in that: The raw materials include the following components in parts by mass: 50-60 parts of silicon dioxide, 15-25 parts of calcium oxide, 5-10 parts of magnesium oxide, 10-15 parts of aluminum oxide, 2-6 parts of zinc pyrostannate, 7-13 parts of zinc hypochlorite, 5-10 parts of iron oxide, 1-3 parts of titanium dioxide, 1-4 parts of phosphorus oxychloride, and 4-9 parts of boron tribromide.

2. The glass-ceramic according to claim 1, characterized in that: The mass ratio of the phosphorus oxychloride and boron tribromide to zinc hypochlorite is 7-12:

9.

3. The glass-ceramic according to claim 2, characterized in that: The mass ratio of the zinc pyrostannate to zinc hypochlorite is 4:

9.

4. The glass-ceramic according to claim 3, characterized in that: The mass ratio of the phosphorus oxychloride to boron tribromide is 1:

3.

5. A process for producing glass-ceramics according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing zinc hypochlorite, phosphorus oxychloride and boron tribromide, heating to 1400-1500°C and then heat preservation, adding the remaining raw materials, and introducing reducing gas for secondary heat preservation to obtain glass liquid; S2, shaping the glass liquid, cooling it to room temperature, heating it to 600-800°C for three times of heat preservation, and cooling it to obtain microcrystalline glass.

6. The production process according to claim 5, characterized in that: The insulation time in S1 is 8 to 15 minutes.

7. The production process according to claim 5, characterized in that: The reducing gas in S1 includes one or both of hydrogen and carbon monoxide.

8. The production process according to claim 5, characterized in that: The secondary insulation time in S1 is 100-120 min.

9. The production process according to claim 5, characterized in that: The molding temperature in S2 is 500-550°C.

10. The production process according to claim 5, characterized in that: The three insulation times in S2 are 40 to 60 minutes.

Citation Information

Patent Citations

  • Boron gettering method for metallurgical N-type polycrystalline silicon chip

    CN102153090A

  • Highly cohesive photovoltaic conductive silver paste

    CN108666004A